Biomarker Data from the Phase III KATHERINE Study of Adjuvant T-DM1 versus Trastuzumab for Residual Invasive Disease after Neoadjuvant Therapy for HER2-Positive Breast Cancer - Denkert, Carsten; Lambertini, Chiara; Fasching, Peter; Pogue-Geile, Katherine L.; Mano, Max S.; Untch, Michael; Wolmark, Norman; Huang, Chiun Sheng; Loibl, Sibylle; Mamounas, Eleftherios P.; Geyer, Charles E.; Lucas, Peter C.; et al. (Clinical Cancer Research, 2023)
PURPOSE: In KATHERINE, adjuvant T-DM1 reduced risk of disease recurrence or death by 50% compared with trastuzumab in patients with residual invasive breast cancer after neoadjuvant therapy (NAT) comprised of HER2-targeted therapy and chemotherapy. This analysis aimed to identify biomarkers of response and differences in biomarker expression before and after NAT. EXPERIMENTAL DESIGN: Exploratory analyses investigated the relationship between invasive disease-free survival (IDFS) and HER2 protein expression/gene amplification, PIK3CA hotspot mutations, and gene expression of HER2, PD-L1, CD8, predefined immune signatures, and Prediction Analysis of Microarray 50 intrinsic molecular subtypes, classified by Absolute Intrinsic Molecular Subtyping. HER2 expression on paired pre- and post-NAT samples was examined. RESULTS: T-DM1 appeared to improve IDFS versus trastuzumab across most biomarker subgroups, except the HER2 focal expression subgroup. High versus low HER2 gene expression in residual disease was associated with worse outcomes with trastuzumab [HR, 2.02; 95% confidence interval (CI), 1.32-3.11], but IDFS with T-DM1 was independent of HER2 expression level (HR, 1.01; 95% CI, 0.56-1.83). Low PD-L1 gene expression in residual disease was associated with worse outcomes with trastuzumab (HR, 0.66; 95% CI, 0.44-1.00), but not T-DM1 (HR, 1.05; 95% CI, 0.59-1.87). PIK3CA mutations were not prognostic. Increased variability in HER2 expression was observed in post-NAT versus paired pre-NAT samples. CONCLUSIONS: T-DM1 appears to overcome HER2 resistance. T-DM1 benefit does not appear dependent on immune activation, but these results do not rule out an influence of the tumor immune microenvironment on the degree of response.
CRIS-Team Scopus Importer:2023-04-28